2002
DOI: 10.1046/j.1365-2222.2002.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator gene mutations: do they play a role in the aetiology of allergic bronchopulmonary aspergillosis?

Abstract: These results lend further support to a possible link between CF mutations and ABPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 33 publications
1
32
1
1
Order By: Relevance
“…ABPA is very common in CF, affecting approximately 15% of all patients (20,21). It is occasionally seen in patients with asthma, although some studies have shown that up to 50% of patients with asthma with ABPA have at least one mutation in the CFTR gene (22)(23)(24)(25). The immune response in ABPA appears to exemplify the IL-4-driven, T helper cell (Th) type 2-predominant response that is seen in patients with CF and in the Cftr mutant mouse expression profiling studies (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…ABPA is very common in CF, affecting approximately 15% of all patients (20,21). It is occasionally seen in patients with asthma, although some studies have shown that up to 50% of patients with asthma with ABPA have at least one mutation in the CFTR gene (22)(23)(24)(25). The immune response in ABPA appears to exemplify the IL-4-driven, T helper cell (Th) type 2-predominant response that is seen in patients with CF and in the Cftr mutant mouse expression profiling studies (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In a genetically predisposed individual [9,10], inhaled conidia of A fumigatus persist and germinate into hyphae with release of antigens that compromise the mucociliary clearance, stimulate and breach the airway epithelial barrier, and activate the innate immunity of the lung [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that mutations in the CFTR gene play a role in a variety of diseases other than classic CF, including CBAVD, 18 chronic pancreatitis, 19 disseminated bronchiectasis, 20 and allergic pulmonary aspergillosis. 21 The CF APEX array can serve as the initial research tool to screen for mutations in these diseases, coupled with other more comprehensive but labor-and capital-intensive technologies if results are negative. As other important disease-contributive CFTR mutations are identified, these can be added to the CF APEX array for routine analysis.…”
Section: Discussionmentioning
confidence: 99%